Management of paratracheal lymph nodes in laryngeal cancer with subglottic involvement. Issue 1 (27th September 2017) - Lucioni, Marco; D'Ascanio, Luca; De Nardi, Elena; Lionello, Marco; Bertolin, Andy; Rizzotto, Giuseppe
Abstract: Background: The purpose of this study was to present our findings on the involvement of paratracheal lymph nodes in laryngeal squamous cell carcinoma (SCC) with subglottis extension, which is controversial. Methods: We assessed 196 patients with laryngeal SCC involving the subglottis, treated with open laryngeal surgery with or without paratracheal neck dissection (PTND). The relationship of the paratracheal lymph node metastatic pattern with laterocervical nodal status and tumor location within different subglottic subsites was analyzed. The influence of PTND on regional disease control was assessed. Results: Paratracheal lymph nodes were affected in 12.2% of cases. An increased frequency ( P  = .064) of paratracheal metastasis was noticed in case of anterior subglottis extension with respect to other subsites. A correlation ( P  < .001) between paratracheal lymph node and laterocervical node involvement was found among subjects with posterior subglottic extension. Conclusions: Prophylactic PTND is indicated in laryngeal SCC with anterior subglottic extension and/or posterior subglottis involvement with clinically apparent laterocervical node metastases.